Measurement bias in self-reports of offending: a systematic review of experiments - Gomes, Hugo S. (2019)
Objectives Self-reported offending is one of the primary measurement methods in criminology. In this article, we aimed to systematically review the experimental evidence regarding measurement bias in self-reports of offending. Methods We carried out a systematic search for studies that (a) included a measure of offending, (b) compared self-reported data on offending between different methods, and (c) used an experimental design. Effect sizes were used to summarize the results. Results The 21 pooled experiments provided evidence regarding 18 different types of measurement manipulations which were grouped into three categories, i.e., Modes of administration, Procedures of data collection, and Questionnaire design. An analysis of the effect sizes for each experimental manipulation revealed, on the one hand, that self-reports are reliable across several ways of collecting data and, on the other hand, self-reports are influenced by a wide array of biasing factors. Within these measurement biases, we found that participants' reports of offending are influenced by modes of administration, characteristics of the interviewer, anonymity, setting, bogus pipeline, response format, and size of the questionnaire. Conclusions This review provides evidence that allows us to better understand and improve crime measurements. However, many of the experiments presented in this review are not replicated and additional research is needed to test further aspects of how asking questions may impact participants' answers.